Use of ICTs: What Effect on the Quality of Youth Employment in Cameroon? - Cosmas Benard Meka'a; Astride Claudel Njiepue Nouffeussie; Romus Noufelie; Gaëlle Tatiana Timba (Center for Economic Studies and ifo Institute (CESifo), 2023)
The objective of this article is to evaluate the effects of Information and Communication Technologies (ICTs) on the quality of youth employment in Cameroon. The study uses data from the Cameroonian Household Survey (CHS 4) carried out by the National Institute of Statistics of Cameroon (NIS) in 2014. The quality of employment is apprehended here by five of its dimensions: income by sector of activity, the nature of the contract, regularity of employment, job satisfaction and length of employment. Our results suggest that young active workers in the formal sector and the informal agricultural sector, demonstrating ICTs skills.
Keywords: J13; J24; J64; J18; 330; ICTs; youth; job quality; heckman model; Cameroon